Hubungan Preeklampsia dan Anemia pada Ibu Hamil dengan Kejadian Berat Badan Lahir Rendah di RSUD Bangkinang - Warningsih, Ayu Dahlia; Syahda, Syukrianti; Harahap, Dewi Anggriani (Evidence Midwifery Journal, 2024)
One of the causes of infant death is due to Low Birth Weight (BBLR). WHO defines babies with a birth weight of less than 2500 grams as low weight, where this condition is at risk of neonatal, post-natal death and higher morbidity than babies born with normal weight. This study was conducted to determine the relationship between preeclampsia and anemia in pregnant women with the incidence of Low Birth Weight at Bangkinang Hospital in 2023. This type of research is quantitative research using a retrospective case control approach research design. The population in this study is all newborn data in 2022 as many as 474 babies. The sample in this study used a ratio of 1: 1, namely 62 with case samples (infants who experienced low birthweight) and 62 with control samples (infants who did not experience low birthweight). The data collection tool in this study used Checklist sheets Data analysis in this study used univariate and bivariate analysis. The results of the study found that there was a relationship between preeclampsia in pregnant women with the incidence of low weight with p value (0.003) and there was a relationship between anemia in pregnant women and the incidence of low weight with p value (0.004). It is hoped that mothers can prepare themselves better to prevent low birth weight by maintaining good nutrition during pregnancy and checking pregnancy regularly with health workers as a form of introspection. Health workers should be able to improve public education and health checks such as Hb and maternal blood pressure so that mothers can better maintain their pregnancies to anticipate low birth weight events.